2018
DOI: 10.1039/c8nj01678j
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of low to high molecular weight poly(1-hexene); rigid/flexible structures in a di- and mononuclear Ni-based catalyst series

Abstract: Poly(1-hexene)s with a wide range of Mw and MWD using mono- and dinuclear rigid/flexible bridged Ni catalysts; structure–property relation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 33 publications
0
33
0
Order By: Relevance
“…D r is the dead polymer and C d is the deactivated site. [51] Polymerization at higher temperature (45 and 65°C) showed a moderate thermal stability of catalyst C 2 . As the first step in the ethylene insertion process is formation of a π-Comp.…”
Section: Ethylene Polymerization Catalyzed By Mononuclear and Dinucmentioning
confidence: 96%
See 3 more Smart Citations
“…D r is the dead polymer and C d is the deactivated site. [51] Polymerization at higher temperature (45 and 65°C) showed a moderate thermal stability of catalyst C 2 . As the first step in the ethylene insertion process is formation of a π-Comp.…”
Section: Ethylene Polymerization Catalyzed By Mononuclear and Dinucmentioning
confidence: 96%
“…As the first step in the ethylene insertion process is formation of a π-Comp. [43,51] 3.2 | Microstructural properties Molecular weight and MWD of mononuclear catalysts (M 1 and M 2 ) correspond to their single-site feature of the center, while for dinuclear catalysts, the presence of stereoisomers afforded different trends in polymerization pathway and products as can be observed in the GPC and short-chain branching (SCB) curves (Figure 4). [45] Although the narrow energy interval (Figure 3) between the precatalyst and catalyst (lower activation energy) led to faster activation (K a ) and coordination for catalyst M 2 having lower steric and electronic effects, catalyst C 2 through optimum bulkiness, synergistic effect and higher stability showed higher K p /K tr and K p /K d rates.…”
Section: Ethylene Polymerization Catalyzed By Mononuclear and Dinucmentioning
confidence: 97%
See 2 more Smart Citations
“…18) with alkyl-and 1,4-phenyl-linked based ligands. 116,117 The ethylene polymerization results using C37b-f suggested that these steric and electronic substituent effects of α-diimine ligands have significant influences on polymerization behaviors. 116 C37a and C37f polymerized 1-hexene to obtain low to high molecular weight poly(1hexene) with M w of up to 1.7 × 10 6 g mol −1 .…”
Section: Dinuclear α-Diimine Nickel and Palladium Catalystsmentioning
confidence: 99%